2000
DOI: 10.1021/jp992137l
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Activated Energy Transfer within Eumelanin Aggregates

Abstract: The emission properties of eumelanin from Sepia officinalis are examined following UV-A excitation. The emission decay is nonexponential, exhibiting decay components on the tens of picosecond to several nanosecond time scales. The corresponding depolarization dynamics are also nonexponential and reveal that the emission becomes totally depolarized with an average time constant of ∼80 ps at 20 °C. The depolarization of the emission is found to be activated; a simple Arrhenius fit to the depolarization rate data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 21 publications
1
43
0
Order By: Relevance
“…This is an important contribution because it suggests that UV radiation with wavelengths below 300 nm generates a longer lived excited state with a significant yield, which in turn may result in excited state photochemistry, which does not occur under visible light stimulation. This photocalorimetric study was followed by additional time resolved measurements, which showed the emission to be depolarised within 80 ps of excitation (Forest et al 2000). Such rapid depolarization is indicative of a high degree of chemical and structural disorder.…”
Section: Physicochemical Properties Of Melaninmentioning
confidence: 94%
See 1 more Smart Citation
“…This is an important contribution because it suggests that UV radiation with wavelengths below 300 nm generates a longer lived excited state with a significant yield, which in turn may result in excited state photochemistry, which does not occur under visible light stimulation. This photocalorimetric study was followed by additional time resolved measurements, which showed the emission to be depolarised within 80 ps of excitation (Forest et al 2000). Such rapid depolarization is indicative of a high degree of chemical and structural disorder.…”
Section: Physicochemical Properties Of Melaninmentioning
confidence: 94%
“…Several such studies indicate that the decay is non-exponential with three or four dominant components on the ns and sub-nanosecond time scale. For example, Forest et al (2000) report four components: c. 60 ps (0.52); c. 0.52 ns (0.22); c. 2.5 ns (0.19); c. 6.9 ns (0.08), where the numbers in brackets is the normalized strength of the component. This emitted radiation represents only a tiny fraction of the total energy absorbed.…”
Section: Time Resolved Fluorescence and Dynamic Studiesmentioning
confidence: 99%
“…Eumelanin is more common in brown-eyed people, while pheomelanin is found in blue-and green-eyed population (Kolb, 2007). The emission decay of melanin is complex, as would be expected from its featureless absorption spectra and the lifetime ranges from picoseconds to almost 8 ns (Forest et al, 2000;Ehlers et al, 2007).…”
Section: Melaninmentioning
confidence: 94%
“…The fitting is omitted for it coincides with the experimental curves. The pre-exponential factors and lifetime constants are listed in Table 2, which also includes the values of Forest et al [35] for eumelanin from sepia officinalis obtained with time-resolved emission at 520 nm and excitation at 335 nm. The parameters in Table 2 for the dynamics of the DPPG + melanin solution are similar to those of eumelanin [35] and for bovine and human eye melanins [36], which were non-degraded.…”
Section: Peakmentioning
confidence: 99%
“…The pre-exponential factors and lifetime constants are listed in Table 2, which also includes the values of Forest et al [35] for eumelanin from sepia officinalis obtained with time-resolved emission at 520 nm and excitation at 335 nm. The parameters in Table 2 for the dynamics of the DPPG + melanin solution are similar to those of eumelanin [35] and for bovine and human eye melanins [36], which were non-degraded. In contrast, for non-incorporated melanin in solution, the parameters differed, with a larger contribution from the fast dynamics (lifetime less than 1 ns) associated with aggregated melanin [36].…”
Section: Peakmentioning
confidence: 99%